2016
DOI: 10.18632/oncotarget.7948
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib inhibits VEGF signaling and promotes apoptosis in intrahepatic cholangiocarcinoma

Abstract: Tumor cells co-express vascular endothelial growth factor (VEGF) and VEGF receptors (VEGFRs) that interact each other to support a self-sustainable cell growth. So far, this autocrine VEGF loop is not reported in human intrahepatic cholangiocarcinoma (ICC). Apatinib is a highly selective VEGFR2 inhibitor, but its effects on ICC have not been investigated. In this study, we reported that VEGF and phosphorylated VEGFR2 were expressed at a significantly high level in ICC patient tissues (P<0.05). In vitro, treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 23 publications
3
91
0
Order By: Relevance
“…32 Recent studies have reported the possible molecular mechanisms involved in the direct anticancer action of apatinib in various cancer cell lines. [33][34][35] These findings suggested that apatinib may also have the potential to directly suppress HCC cell growth. As shown in the present study, the expression of VEGFR-2 was markedly higher in 6 HCC cell lines compared to normal controls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…32 Recent studies have reported the possible molecular mechanisms involved in the direct anticancer action of apatinib in various cancer cell lines. [33][34][35] These findings suggested that apatinib may also have the potential to directly suppress HCC cell growth. As shown in the present study, the expression of VEGFR-2 was markedly higher in 6 HCC cell lines compared to normal controls.…”
Section: Discussionmentioning
confidence: 90%
“…VEGF/VEGFR signaling is required in tumor cells to stimulate their proliferation and invasive growth in an autocrine and angiogenesis‐dependent manner . Recent studies have reported the possible molecular mechanisms involved in the direct anticancer action of apatinib in various cancer cell lines . These findings suggested that apatinib may also have the potential to directly suppress HCC cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib, also known as YN968D1, is a small molecule TKI that mainly targets VEGFR‐2 through the intracellular ATP‐binding site that inhibits all VEGF‐stimulated endothelial cell migration and proliferation, decreases tumor microvascular density, and promotes apoptosis . On 17 October 17, 2014, apatinib was approved by the cFDA as a third or subsequent‐line therapy for advanced or metastatic chemo‐refractory gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Apatinib, also known as YN968D1, is a small molecule TKI that mainly targets VEGFR-2 through the intracellular ATP-binding site that inhibits all VEGF-stimulated endothelial cell migration and proliferation, decreases tumor microvascular density, and promotes apoptosis. [46][47][48] On 17 October 17, 2014, apatinib was approved by the cFDA as a third or subsequent-line therapy for advanced or metastatic chemo-refractory gastric cancer. 49 Both preclinical and clinical studies have shown that apatinib has promising efficacy, convenient oral administration methods, and manageable AEs in the treatment of a variety of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib was obtained from Jiangsu Hengrui Medicine Co. Purified water was produced by a Milli-Q system (Millipore). [1,[2][3][4][5][6][7][8][9][10][11][12][13] C 2 ] Myristic acid, methoxyamine hydrochloride (purity 98%), alkane solution (C8-C40), and pyridine (99.8% GC) were purchased from Sigma-Aldrich. MSTFA (N-methyl-N-trimethylsilyltrifluoroacetamide) and 1% TMCS (trimethylchlorosilane) were obtained from Pierce Chemical Company.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%